Peran Customer-Based Brand Equity Terhadap Peningkatan Customer Satisfaction Dan Brand Loyalty Pada Djournal Coffee - Annisaa Leonida Regi; Santi Rimadias; Lediana Sufina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This study aims to examine and analyze the role of customer-based brand equity in increasing customer satisfaction and brand loyalty in Djournal Coffee. The field survey was conducted on 125 Djournal Coffee customer respondents located in the DKI Jakarta area. The proposed model is evaluated using structural equation analysis. The results show that customer satisfaction plays the most important role in creating brand loyalty for Djournal Coffee customers. Physical quality, staff behavior, and lifestyle-congruence which are part of customer-based brand equity can drive increased customer satisfaction. However, ideal self-congruence and brand identification have no effect on customer satisfaction. With limited research on the buying behavior of coffee shop customers, these findings can be used meaningfully to increase brand loyalty.